EFFICACY OF ULTRAVIOLET-C IRRADIATION TO SUPPRESS FRUIT DECAY AND RETAIN THE POSTHARVEST QUALITY OF DRAGON FRUIT (Hylocereus polyrhizus) - NG, LEE CHUEN; TAN, JACK SINK; FAUZIAH, TUFAIL AHMAD (Malaysian Applied Biology, 2022)
Dragon fruit (Hylocereus sp.) is a non-climacteric fruit with a short shelf-life and is easily susceptible to diseases. Chemical pesticides are commonly used to control disease in dragon fruit. However, the efficacy of Ultraviolet-C (UV-C) irradiation at low concentrations as effective germicidal to control fruit decay and prolong the shelf-life on dragon fruit is still unexplored. This study aimed to evaluate the efficacy of UV-C irradiation at lower rates (0, 0.25, 0.5, 0.75, 1.0 kJ m-2) to control the postharvest decay and maintain the quality of dragon fruit. Results revealed that the quality of dragon fruit is dose-dependent. UV-C irradiated dragon fruits at 0.75 and 1.0 kJ m-2 were significantly reduced in fruit body decay, delayed bract yellowing, and prolonged shelf-life. These dosages synergistically slowed down the depletion of total soluble solids and fruit firmness during storage. Also, dragon fruit treated with 1.0 kJ m-2 UV-C exhibited the lowest pH value after the 6th day in storage. UV-C irradiation at this dosage indicated no significant adverse effects in titratable acidity and total water loss. These results indicated that UV-C irradiation at 1.0 kJ m-2 was effective to reduce post-harvest decay and hence prolong the post-harvest quality of dragon fruit storage under ambient conditions.